2013
DOI: 10.1371/journal.pone.0063819
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate Microneedle Arrays Mediate the Transdermal Delivery of Bovine Serum Albumin

Abstract: BackgroundThe “poke and release” strategy for the delivery of macromolecules using polymeric microneedle (MN) is of great importance because it eliminates microneedle reuse, the risks of biohazardous sharps and cross contamination, and it requires no special disposal mechanism. The main objective of this study was the determination of the stability and delivery of bovine serum albumin (BSA) that was transported across human skin via sodium alginate (SA) microneedle arrays (MNs) and SA needle free patches using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Demir et al used sodium alginate microneedles to deliver BSA across the skin and found a 15.4-fold improvement in permeation compared to needle free sodium alginate patches. [42] Chen et al reported that BSA loaded chitosan microneedle patches led to sustained release of BSA for 8 d while Lee et al and Sullivan et al demonstrated that microneedles that "dissolve" in the skin could be used for transdermal delivery of BSA and lysozyme. [43][44][45] Prausnitz et al encapsulated influenza vaccine in dissolving microneedle patches made from polyvinylpyrrolidone and found that the vaccine was not only stable long-term but also was effectively delivered across the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al used sodium alginate microneedles to deliver BSA across the skin and found a 15.4-fold improvement in permeation compared to needle free sodium alginate patches. [42] Chen et al reported that BSA loaded chitosan microneedle patches led to sustained release of BSA for 8 d while Lee et al and Sullivan et al demonstrated that microneedles that "dissolve" in the skin could be used for transdermal delivery of BSA and lysozyme. [43][44][45] Prausnitz et al encapsulated influenza vaccine in dissolving microneedle patches made from polyvinylpyrrolidone and found that the vaccine was not only stable long-term but also was effectively delivered across the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dissolvable sodium alginate (SA) and hydroxypropyl cellulose (HPC) (H and M grades), swellable physically cross-linked polyvinyl alcohol (PVA) and gelatin hydrogels, biodegradable chitosan and PLGA polymers were used to fabricate solid, out-of-plane, polymeric MNs from pyramidal male master templates of the following dimensions: 900-ìm height (700-ìm column height and 200-ìm pyramid tip height), 250-ìm needle base width, 500-ìm interneedle base spacing, and 100-ìm apex diameter [40], [41].…”
Section: Introductionmentioning
confidence: 99%
“…1h), where overall a spin-casting method was mainly used. 2,17,18) Scanning electron microscopy (SEM) analysis of pectin MNs, differential scanning calorimetry (DSC) analysis of pectin MNs, bovine serum albumin (BSA)/pectin MNs interaction studies with bicinchoninic acid (BCA) method, BSA/ pectin MNs were performed to the similar of our earlier publication. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4,5) Although the first silicon MNs were of being too brittle and possessing non-biocompatible nature, 6,7) intensive research since then has yielded many pharmaceutical, polymer-based MN systems as alternatives. 2,[8][9][10][11][12][13][14][15][16] Micro manufacturing techniques, 17,18) deduction of suitable polymers for MNs and optimization of the formulation parameters to produce MNs that possess characteristics like solubility, swelling, and biodegradability were previously published. 8) Polymeric MNs have great potential to start a million dollar market up by revolutionizing not only the drug delivery systems (conventional transdermal patches and hypodermic needles), but also drug monitoring devices (both bench top and portable systems).…”
mentioning
confidence: 99%